2020
DOI: 10.1016/j.conx.2020.100033
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the extent of contraceptive non-use among women at risk of unintended pregnancy, National Survey of Family Growth 2011–2017

Abstract: Objective To describe characteristics of U.S. contraceptive non-users to inform tailored contraceptive access initiatives. Study design We used National Survey of Family Growth data from 2011 to 2017 to identify characteristics of contraceptive non-users compared to other women ages 15–44 at risk for unintended pregnancy. We also examined reasons for not using contraception by when non-users expected their next birth. We calculated unadjusted and adjusted prevalence rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…” We determined contraceptive use status according to whether respondents reported using any contraceptive method during the month of survey interview (current users) or not (nonusers of contraception). We maintain distinctions between contraceptive users and nonusers of contraception in examining our outcome of interest due to key differences in demographic and sexual and reproductive health (SRH) characteristics between these 2 groups [7] , which may have implications for our analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…” We determined contraceptive use status according to whether respondents reported using any contraceptive method during the month of survey interview (current users) or not (nonusers of contraception). We maintain distinctions between contraceptive users and nonusers of contraception in examining our outcome of interest due to key differences in demographic and sexual and reproductive health (SRH) characteristics between these 2 groups [7] , which may have implications for our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In a 2020 national study, 25% of women who were not using their preferred method of contraception indicated that it was because they could not afford it [6] . Among women at risk of unintended pregnancy in the United States, nonusers of contraception are more likely to have lower incomes and be uninsured compared to users [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Using a national database, this study was able to detect small associations and have increased generalizability. Prior publications using this database addressed different perspectives on childbirth, sexual behavior, and contraceptive use 1,23,25,45–47 . The current analysis explicitly focused on factors associated with LARC use.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, five articles affirmed that women in larger bodies’ contraceptive non-use was often associated with perceived subfertility [ 42 , 56 , 57 , 59 , 65 ]. Parallel to these findings, perceived infertility has been identified as one of the leading reasons for contraceptive non-use among American women at risk of unintended pregnancy [ 74 ]. Although having a BMI ≥ 30 is associated with an elevated risk of fertility issues and miscarriage [ 75 ], studies with women who consider themselves to be less likely to become pregnant have yet to attribute this perception to weight or body size [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%